Strengthening the Profile of Pancasila Students Through Cultural Values in Folklores of Ponorogo - Suprapto, Suprapto; Rois, Syamsudin (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
The current era is marked by a concerning trend of moral degradation among the younger generation. This current study aims to describe and explain the cultural values embedded in Ponorogo's folklore and examine the relevance of this folklore as teaching materials for strengthening the Pancasila Student Profile. The researchers employed a qualitative research method. To collect information, the researchers used primary and secondary sources related to the folklore of Ponorogo. Data analysis followed Miles and Huberman's interactive model, which involved data reduction, display, verification, and interpretation to draw meaningful conclusions. Triangulation was used to ensure data trustworthiness. The study results revealed that the cultural values based on local wisdom/folklore embedded in Ponorogo include religious, mutual help, morals, customs, and historical values. Furthermore, the relevance between the folklore of Ponorogo and local wisdom values can be utilized as learning materials in elementary schools. As a result, it can strengthen the Pancasila student profile, enabling students to develop critical thinking, independence, intelligence, moral character, cultural awareness, and nobility from an early age.